2015
DOI: 10.1210/me.2015-1028
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk Between GH-Regulated Transcription Factors HNF6 and CUX2 in Adult Mouse Liver

Abstract: Hepatocyte-enriched nuclear factor (HNF)6 and CUX2 are GH and STAT5-regulated homeobox transcription factors. CUX2 shows female-specific expression and contributes to liver sex differences by repressing many male-biased genes and inducing many female-biased genes, whereas HNF6 is expressed at similar levels in male and female liver. In cell-based transfection studies, CUX2 inhibited HNF6 transcriptional regulation of the sex-specific gene promoters CYP2C11 and CYP2C12, blocking HNF6 repression of CYP2C11 and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 59 publications
(108 reference statements)
2
52
0
Order By: Relevance
“…4C). Enrichment of both CUX2 and ONECUT (also named HNF6) is consistent with ONECUT1 binding to both ONECUT and CUX2 motifs (Conforto et al 2015). mRNAs of genes with co-occurrence of RORE and liver-specific TF motifs peaked near ZT1, consistent with peak RORE activity (near ZT21) preceding peak mRNA abundance of REV-ERB targets (Supplemental Fig.…”
Section: Combinatorics Of Rhythmic Transcript Expression Across Tissusupporting
confidence: 60%
“…4C). Enrichment of both CUX2 and ONECUT (also named HNF6) is consistent with ONECUT1 binding to both ONECUT and CUX2 motifs (Conforto et al 2015). mRNAs of genes with co-occurrence of RORE and liver-specific TF motifs peaked near ZT1, consistent with peak RORE activity (near ZT21) preceding peak mRNA abundance of REV-ERB targets (Supplemental Fig.…”
Section: Combinatorics Of Rhythmic Transcript Expression Across Tissusupporting
confidence: 60%
“…Male-biased binding of four GH-regulated transcriptional activators, STAT5, FOXA1, FOXA2, and HNF6 (53,54,56), was significantly enriched at sites near (within 10 kb) the set of 85 stringent (i.e., GH-regulated) male-specific lincRNAs and was significantly depleted near the set of 86 stringent female-specific lincRNAs lincRNAs that had an ortholog in at least 1 of the 10 species investigated. The orthologs were required to span Ն10% of the full-length, mature mouse lincRNA transcript and to be Ն600 bp in length (see Materials and Methods).…”
Section: Identification Of Liver-expressed Lincrnasmentioning
confidence: 95%
“…We investigated whether sex-specific lincRNA genes are enriched for nearby sites of sex-dependent chromatin accessibility, which bind TFs in a sex-dependent manner (54)(55)(56) and can be detected as sex-biased DHS (52). We found that the stringent (i.e., GH-regulated) male-specific lincRNAs are significantly enriched for nearby (within 10 kb) male-biased DHS (P ϭ 5.77eϪ11) and depleted of female-biased DHS.…”
Section: Identification Of Liver-expressed Lincrnasmentioning
confidence: 96%
See 2 more Smart Citations